2017
DOI: 10.3126/jpn.v7i1.16944
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sepsis Screening in early diagnosis of Neonatal Sepsis

Abstract: Background: Neonatal sepsis, a clinical syndrome of bacteremia with systemic signs and symptoms of infection in the first 4 weeks of life is a major cause of morbidity and mortality in newborn inborn. Early diagnosis is critical, as sepsis can progress more rapidly in neonates than in adults. An attempt was made to establish correlation between early neonatal sepsis screening & blood culture in neonates presenting with features of sepsis. The aim of this study is to assess the usefulness of sepsis screen in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 15 publications
5
20
2
Order By: Relevance
“…The most common clinical manifestation of neonatal sepsis in our study was respiratory distress (79%). Similar findings were noted in studies from KIST Medical College, Nepal (54%) and Beni Suef University Hospital, Egypt (36%) [9,12]. At our center, we take CRP as a biomarker of sepsis and its serial decline is taken as laboratory evidence of improvement.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The most common clinical manifestation of neonatal sepsis in our study was respiratory distress (79%). Similar findings were noted in studies from KIST Medical College, Nepal (54%) and Beni Suef University Hospital, Egypt (36%) [9,12]. At our center, we take CRP as a biomarker of sepsis and its serial decline is taken as laboratory evidence of improvement.…”
Section: Discussionsupporting
confidence: 72%
“…However, our study, which is first of its kind to be conducted in NICU of the same institute, showed culture positivity of neonatal sepsis to be 20.7%. In contrast, studies conducted at KIST Medical College and Manipal College of Medical Sciences, Nepal showed culture positivity to be 48 and 44.9% respectively [9,10]. Variations in culture positivity rate of neonatal sepsis in different studies seem to arise from differences in culture-techniques and study designs.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast to the present study, Zaka-ur-Rab Z et al found that amongst individual markers of sepsis screen, CRP had good diagnostic utility with highest sensitivity (82%) and specificity (89%) [18]. Lakhey A et al found that CRP (78%) and IT ratio (73%) had highest sensitivity [21].…”
Section: Original Research Articlecontrasting
confidence: 90%
“…A study done by Lakhey et al, in Nepal found respiratory distress (56%), fever (26%) and feeding problems (12.6%) the most common clinical features. 15 EOS generally presents itself with respiratory distress, apnea, lethargy or irritability, temperature instability, and feeding difficulties. 16 Overall the most common organism isolated was CONS (27%) followed by Klebsiella (24%) and Staphylococcus aureus (18%).…”
Section: Resultsmentioning
confidence: 99%